ACM SIGGRAPH 2005 Papers 2005
DOI: 10.1145/1186822.1073279
|View full text |Cite
|
Sign up to set email alerts
|

The Varrier TM autostereoscopic virtual reality display

Abstract: Virtual reality (VR) has long been hampered by the gear needed to make the experience possible; specifically, stereo glasses and tracking devices. Autostereoscopic display devices are gaining popularity by freeing the user from stereo glasses, however few qualify as VR displays. The Electronic Visualization Laboratory (EVL) at the University of Illinois at Chicago (UIC) has designed and produced a large scale, high resolution headtracked barrier-strip autostereoscopic display system that produces a VR immersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Gabriel Lippmann [1908] and Frederic Ives [1903] were the first to discover how arrays of lenslets or pinholes can be used to synthesize a light field. These technologies have evolved into head-tracked [Perlin et al 2000] and largescale multi-monitor [Sandin et al 2005] systems. However, one of the main shortcomings of these approaches is the loss of image resolution-spatial resolution is traded for angular light field resolution.…”
Section: Related Workmentioning
confidence: 99%
“…Gabriel Lippmann [1908] and Frederic Ives [1903] were the first to discover how arrays of lenslets or pinholes can be used to synthesize a light field. These technologies have evolved into head-tracked [Perlin et al 2000] and largescale multi-monitor [Sandin et al 2005] systems. However, one of the main shortcomings of these approaches is the loss of image resolution-spatial resolution is traded for angular light field resolution.…”
Section: Related Workmentioning
confidence: 99%
“…Markerless, head-tracked, auto-stereo displays has been demonstrated [58]. Non-encumbering input further implies using held devices and/or using gloveless hand and finger tracking which precludes haptic feedback.…”
Section: 5mentioning
confidence: 99%
“…Building on this hardware configuration, the synergy among the cluster nodes ensures that pixel rendering across all the tiles are coordinated to provide the user with a large "single" screen experience. Cluster-driven large displays can be a projection-based wall (Mechdyne, 2008), flat panel-based wall (Jeong et al, 2006;Sandin et al, 2005;Sandstrom et al, 2003) or flat panel-based tabletop (Krumbholz et al, 2005). Two detailed reviews of recent progress on large displays can be found in (Wallace et al, 2005) and (Ni et al, 2006).…”
Section: Background Of the Applicationmentioning
confidence: 99%
“…In the mean time, the CPU performance of each node is growing exponentially with Moore's Law. For example, Varrier (Sandin et al, 2005), a 35-tile system uses an 18-node cluster. While Hyperwall (Sandstrom et al, 2003), a 49-tile system uses a 49-node cluster.…”
Section: Background Of the Applicationmentioning
confidence: 99%